Accounting Practices and the Market Valuation of Accounting Numbers: Evidence from Indonesia, Korea, Malaysia, the Philippines, Taiwan, and Thailand - Graham,Roger; King,Raymond D. (International Journal of Accounting, 2000)
This study examines the relation between stock prices and accounting earnings and book values in six Asian countries: Indonesia, South Korea, Malaysia, the Philippines, Taiwan, and Thailand. The analysis is based on a residual earnings model that expresses the value of the firm in terms of book value and residual income. The model holds for any clean surplus accounting system. However, for finite time horizons, biased accounting may affect model estimates. The six countries examined in this study differ in faithfulness to clean surplus accounting as well as bias (conservatism). The study addresses two questions. First, are there systematic differences across countries in the value relevance of accounting, and are these differences related to accounting differences? Second, are there systematic differences in the incremental and relative information content of book value per share (BVPS) and abnormal (residual) earnings per share (REPS) across the countries, and are such differences related to accounting differences? We find differences across the six countries in the explanatory power of BVPS and REPS for firm values. Explanatory power for Taiwan and Malaysia is relatively low while that for Korea and the Philippines is relatively high. These differences are generally consistent with differences in accounting practice; however, since Korean accounting practice is strongly influenced by tax law, we did not expect the high association for Korea. Second, with respect to the incremental and relative explanatory power of BVPS and REPS, we find BVPS to have high explanatory power in the Philippines and Korea but little in Taiwan. In all six countries REPS has less explanatory power than BVPS in most years. Again, the evidence may be interpreted as suggesting accounting practice affects valuation (with Korea again as the exception). Finally, we provide evidence on the sensitivity of the timing of comparisons of stock prices and accounting values. We find that comparing prices at year-end (even though annual accounting information has not been released at that time), in general, provides the highest correlation between market and accounting numbers.
Keywords: Accounting